2004
DOI: 10.1007/s00109-004-0549-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting multiple signal transduction pathways through inhibition of Hsp90

Abstract: The multichaperone heat shock protein (Hsp) 90 complex mediates the maturation and stability of a variety of proteins, many of which are crucial in oncogenesis, including epidermal growth factor receptor (EGF-R), Her-2, AKT, Raf, p53, and cdk4. These proteins are referred to as "clients" of Hsp90. Under unstressed conditions these proteins form complexes with Hsp90 and the cochaperones to attain their active conformations or enhance stability. Inhibition of Hsp90 function disrupts the complex and leads to degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
354
0
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(367 citation statements)
references
References 70 publications
6
354
0
7
Order By: Relevance
“…21 In addition to GA and 17-DMAG, HSP90 can also be inhibited by novobiocin, epigallocatechin gallate, cisplatin and others. 22,23 These alternative inhibitors differ from GA and 17-DMAG in that they exert additional effects on cellular mechanisms beyond the blockade of HSP90. 24 Recently, a synthetic HSP90 inhibitor (EC144) was found to decrease disease severity in mouse and rat models of induced arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…21 In addition to GA and 17-DMAG, HSP90 can also be inhibited by novobiocin, epigallocatechin gallate, cisplatin and others. 22,23 These alternative inhibitors differ from GA and 17-DMAG in that they exert additional effects on cellular mechanisms beyond the blockade of HSP90. 24 Recently, a synthetic HSP90 inhibitor (EC144) was found to decrease disease severity in mouse and rat models of induced arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, almost all the known clients of the molecular chaperone Hsp90 (90 kDa heat-shock protein), including many important kinases and transcription factors, are found to be degraded by the proteasome when Hsp90 is inactivated by its specific inhibitor geldanamycin (GA), an anti-tumor drug [17][18][19]. On the other hand, the role of macroautophagy (simply referred to as autophagy hereafter) in the regulation of Hsp90 clients and specific signaling pathways remains largely unknown, although this mode of lysosome-dependent degradation is well-known to be the primary mechanism other than the proteasome employed for protein degradation within eukaryotes [19].…”
Section: Introductionmentioning
confidence: 99%
“…For reasons that are unclear, malignant cells seem to depend more than normal cells on Hsp90 and consequently display selective sensitivity to Hsp90 inhibition. Early clinical trials of ansamycins in solid tumours have indicated an acceptable toxicity profile, and efforts are now being focused on evaluating their effectiveness against different malignancies (Workman, 2004;Zhang and Burrows, 2004). With regard to the therapeutic potential of Hsp90 inhibition in CLL, two previous reports have shown that cultured CLL cells are sensitive to ansamycin treatment, and that this may involve depletion of the Hsp90 client proteins Akt (Jones DT et al, 2004) or ZAP-70 (Castro et al, 2005).…”
Section: Introductionmentioning
confidence: 99%